What Do Indonesian Think About Waqf? A Sentiment Analysis Using Machine Learning (ZISWAF: Jurnal Zakat dan Wakaf, 2023)
This study aims to identify the most popular topics and words in conversations on Twitter with the topic of waqf in Indonesia. This study also aims to identify the sentiments and emotions of netizens about waqf in Indonesia. This study uses a qualitative method with a sentiment analysis approach with the help of Orange Data Mining. The data used are tweets from Twitter taken from April 10, 2023, to April 24, 2023. Researchers used the keyword "Wakaf" to get 1,000 tweets. The results of the study show that the words "Wakaf," "Masjid," and “Tanah" are the three words that most often appear in discussions on the topic of waqf on Twitter. These three words refer to the people in Indonesia, where the majority donate part of their wealth in the form of land designated as a mosque. On social media, Twitter is dominated by tweets with neutral sentiments shown by happy emotions, as much as 76.37% of the total tweets. Waqf management institutions can increase the intensity of using social media in publicizing activities related to collecting waqf donations and managing and distributing the benefits of waqf funds to mauquf alaih as a form of transparency to increase the credibility of waqf management institutions.